An early experience of COVID‐19 disease in pediatric and young adult renal transplant recipients. (27th January 2021) - Solomon, Sonia; Pereira, Tanya; Samsonov, Dmitry
Abstract: Background: COVID‐19 is caused by a novel form of coronavirus known as SARS‐CoV‐2. Patients can present with a wide variety of symptoms from fever to severe respiratory distress. Immunocompromised patients, including solid organ transplant recipients, may present with atypical symptoms, making the diagnosis of COVID‐19 more difficult to make. New reports have been emerging about the management of COVID‐19 disease in adult renal transplant recipients. However, very little is known in pediatric renal transplant recipients. Methods: Here, we describe a case report of four pediatric renal transplant recipients who presented with mild‐to‐moderate COVID‐19 disease. Results: All patients presented with upper respiratory infection symptoms, with one requiring hospitalization for hypoxia. Patients were treated mostly with supportive care. Two of the patients developed AKI which resolved four to eight weeks after illness. All four patients developed COVID IgG antibodies one to two months after becoming infected. Conclusion: This case series demonstrates that immunocompromised renal transplant recipients have comparable outcomes compared with immunocompetent children.